LIFE SKILLS EDUCATION TRAINING FOR SANTRI IN ISLAMIC BOARDING SCHOOL (Universitas Negeri Semarang, 2015)
One way to achieve an effective education is by implementing life skills education in every level of formal and informal education. Most education in Islamic boarding schools (Pondok Pesantren) has not developed life skills education although life skills education is very important for the students (santri). The study aims at describing the factual model of life skills education training management, designing a model of life skills education training management based on local potential, determining the validity of the conceptual model of management training, and determining the effectiveness of the management model of life skills training. This study employed research and development (R & D). The stages of R & D in this study included: preliminary studies, model development, model validation, and testing the model. Research data collection techniques used interviews, documentation, observation and questionnaires. The validity was measured using triangulation technique and experts validation. Test model was conducted through a limited testing and expanded trials for 20 santris at Pesantren Miftahul Huda Pulokulon Grobogan in March 2014. The results show that the final model of the life skills education training has higher efficacy. Life skill education training model based on local potential can improve the competence of santris in independently developing life skill, especially in improving knowledge, skills and attitudes of santri in the development of their life skill. The results could be used by a Pondok Pesantrenl or other educational institutions to provide life skill education training independently, easily and quickly.